Provision of POC Coconut Water and Tea Dregs Compost on Plant Growth and Production - Erwin Pane; Saipul Sihotang; Marco Y. F Sitompul; Asmah Indrawaty; Merlyn Mariana; Adi Fathul Qohar (Postgraduate, University of Mataram, 2023)
The aims ofthis research is to determine the response of growth and production of sweet corn (Zea Mays Saccharata Strurt) to the application of liquid organic fertilizer coconut water and tea waste compost. The research cobducted in Trial Garden of Agriculture Faculty of Medan Area University, Kolam Street no 1 Medan Estate with height 22 m above sea level. Plat topografi and alluvial soil type was done since June up to September 2018. The research is using Random Designing Group Factorial with two factors, such as coconut water POC (K0 = Control (purn); K1 = coconut water POC 50 ml/L; K2 = coconut water POC 100 ml/L; K3 = coconut water POC 150 ml/L), and the giving factors of tea pulp compost (K0 = Control (purn); K1 = tea pulp compost 5 Ton/Ha; K2 = tea pulp compost 10 Ton/Ha; K3 = tea pulp compost 15 Ton/Ha). Repeatedly twice. Parameter which observed are the height of the plant, leaf amount, diameter of the stem, the sample each plot of plant production, plant production each plot. The result of this research is two show that the giving of coconut water POC is not really influencing to the treatment and giving of the tea pulp compost to the treatment and giving of the tea pulp compost is really influencing to the height of the plant, the sample of plant production each plot, plant production each plot but not really influence to the leaf amount and diameter of stem as well as combination among coconut water POC and tea pulp compost is not influencing to all treatments.